Hubungan Nature Relatedness dan Perilaku Membuang Sampah Sembarangan oleh Mahasiswa - Agatha, Jeannette Tirza Remalya; Kefi, Angelina Indriani; Gultom, Tiur Angelina; Antasya, Janriani Desanta; Witjaksono, Rahadian Naufal; Adiwena, Bartolomeus Yofana (Fakultas Psikologi Universitas Sanata Dharma, 2024)
The existence of waste is very influential on the environment and living things. One of the most common environmental problems is the behavior of littering. The campus is one of the places where we often find the behavior of littering indiscriminately. Factors that are thought to be related to littering are nature relatedness. Nature relatedness is a person's level of attachment to his environment. The purpose of this study was to find out whether there is a relationship between a person's nature relatedness to the behavior of littering among students. This research is a correlational quantitative research with 74 respondents obtained by incidental sampling method. The results showed that there was no significant relationship between a person's nature relatedness and littering behavior (r= 0.212; p=n.s). These results can prove to us that a person's nature relatedness does not necessarily make them behave eco-friendly. This insignificant result can be a good indication of eco- friendly behavior in the campus environment.